Molecular basis for the plasticity of aromatic prenyltransferases in hapalindole biosynthesis - Awakawa, Takayoshi; Abe, Ikuro (Beilstein Journal of Organic Chemistry, 2019)
Aromatic prenyltransferases (PTases) are enzymes that catalyze Friedel–Crafts reactions between aromatic compounds and isoprenoid diphosphates. In hapalindole biosynthesis, the aromatic PTases AmbP1 and AmbP3 exhibit surprisingly plastic selectivities. AmbP1 not only transfers the geranyl group on the C-3 of cis-indolylvinyl isonitrile, but also on the C-2, which is supressed in the presence of Mg2+ ions. AmbP3 transfers the dimethylallyl group on C-2 of hapalindole U in the reverse manner, but on C-2 of its C-10 stereoisomer in the normal manner. This review highlights the molecular bases of the AmbP1 and AmbP3 functions, elucidated through their X-ray crystal structures. The knowledge presented here will contribute to the understanding of aromatic PTase reactions and will enhance their uses as biocatalysts.
Keywords: crystal structure; cyanobacteria; Friedel–Crafts reaction; hapalindole; prenyltransferase